S209. DRUG-NAïVE FIRST-EPISODE SCHIZOPHRENIA SPECTRUM DISORDERS: PHARMACOLOGICAL TREATMENT PRACTICES IN INPATIENT UNITS IN HUNAN PROVINCE, CHINA. (18th May 2020) - Zhu, Mengran; Ferrara, Maria; Tan, Wenjian; Shang, Xingbo; Syed, Sumaiyah; Zhang, Li; Qin, Qilin; Srihari, Vinod; Liu, Zhening
Abstract: Background: Antipsychotics represent the core of treatment for first-episode schizophrenia (FES). The choice of the first antipsychotic in drug-naïve FES patients is delicate, as it could influence both adherence to medications and the course of the illness. In China, mental health care for schizophrenia is mainly provided by psychiatric hospitals, due to the limited resources in outpatient community care. Psychiatrists and nurses are the main providers of mental health care, and medication is becoming the primary intervention for mental illness. In 2015, the second edition of China's Guidelines for Schizophrenia was released. The use of a minimum effective dose of a single antipsychotic has been indicated for FES, consistent with multiple international guidelines. Since the current treatment practice for FES in China is unknown, this study aimed to describe antipsychotic prescription patterns for drug-naïve FES inpatients, and factors associated with practices deviating from China's current guidelines. Methods: This was a retrospective study. Participants included all inpatients, ages 7 to 45 years, experiencing a first episode of schizophrenia-spectrum disorder with a duration of untreated illness (interval between onset of psychotic symptoms and first antipsychotic prescription) less than 18 months, admitted between Aug 1st, 2016 and Aug 1st, 2017 to one of eight hospitals in Hunan Province. Demographics, clinical characteristics, and prescriptions at discharge were collected from electronic medical records. Descriptive analysis was used to describe prescription patterns. Logistic regression and random forest methods were used to model relationships between factors and deviations from China's guidelines. Results: Of the 602 inpatients included in the study, 598(99.3%) were prescribed antipsychotics at discharge, mostly risperidone (41.8%) and olanzapine (41.0%). Polytherapy (being prescribed more than one antipsychotic) was present in 121 (20.2%) participants. The prescription rate of high-dose antipsychotics among adults was 32.9%, and of off-label antipsychotics among minors was 23.2%. Adults (OR=1.95, 95% CI: 1.14–3.34, compared to minors) and patients with longer length of stay (OR=1.09, 95% CI: 1.03–1.14) were more likely to receive polytherapy. Younger age (OR= 0.96, 95% CI 0.93–0.99), having non-tertiary hospitalization (OR=0.38, 95% CI 0.24–0.59, compared to tertiary hospitalization), and being prescribed polytherapy (OR= 3.56, 95% CI 2.17–5.86, compared to monotherapy) were associated with high-dose antipsychotics prescription. Participants younger than 13 were more likely to receive off-label antipsychotics. Clozapine was prescribed to 45 (7.5%) patients, and more frequently to those hospitalized in non-tertiary facilities (χ2= 8.606, P=0.003) and receiving polytherapy (χ2= 81.488, P<0.001). Patients receiving clozapine had longer length of stay than those who did not (mean (SD): 8.02(4.93) vs 4.35(4.18) weeks, P<0.001). Discussion: Our study showed that most of the FES inpatients were prescribed antipsychotic in monotherapy, in compliance with current guidelines. Deviations from guidelines were found in younger patients with schizophrenia, and in clozapine prescriptions. Different practices were observed between tertiary and non-tertiary hospitals, suggesting possible challenges in delivering mental health care in those facilities where disproportionate distribution of resources might happen. Given the ongoing implementation of the National Mental Health Working Plan, these results provide a useful representation of the current practice in China and could help decision-makers on resource allocation in order to promote the best treatment for first-episode psychosis.